ANALISIS KOMPONEN UNGGULAN SUMBER PENDAPATAN ASLI DAERAH (PAD) KABUPATEN KAYONG UTARA - B2051131002, SADIKIN (Jurnal Ekonomi Daerah (JEDA), 2016)
This Research entitled â€œAnalysis Main Component Of Local Revenue Sources Of North Kayong Regencyâ€, is a case study in Kayong Utara Regency and West Kalimantan. The aim of research is to determine and analyze the featured components of Loca source of revenue (PAD) and the competitiveness of the district of Kayong Utara Regency and create or formulate strategies policies in increased local revenue (PAD). The method of analysis is typolgi Klasen, by looking at the contribution and growth of each component of revenue (taxes and retribution) Â and compare it with the the same component/variable in the regional in West Kalimantanthen segmenting each variable (component PAD) as income prime, potential, developing and underdeveloped for TPI. The result shownÂ  the Components ofÂ  KKU PAD consistsof 8 types of local taxes and 16 types of retribution. Based on calculations typology Klassen Typology does not have a tax component which prima (above average Kalbar both growth and contribution), but there are still potential components and thrive, namely tax non-metallic minerals and rocks and amusement tax is a component of the PAD's most advanced and growing because it has the highest growth over five years for the establishment of the Kayong Utara Regency. Advertisement tax, hotel tax and BPHTB including potential. While Groundwater tax, restaurant tax, and entered the category of street lighting tax retarded. The retribution manage is relatively better, Â from 16 types of retribution 9 item (56.25%) is prime, crossing water, recreation and sports, SITU, SIUP, TDP, Fishery and nuisance permit, Potential retribution including port services, and the fish auction levy. The Â developing is Askes PNS on health services, and testing of motor vehicles, as well as include the category is roadside parking services general, terminal and IMB. Keywords: local taxes, retribution area, PAD, featured.